1982
DOI: 10.1002/1097-0142(19820101)49:1<80::aid-cncr2820490118>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

LDH isoenzyme patterns in tumors, polyps, and uninvolved mucosa of human cancerous colon

Abstract: By using a method of electrophoresis separation, the authors determined the relative values of each one of the lactic dehydrogenase (LDH) isoenzymes in the normal colonic mucosa. In adenocarcinomas, there is a significant rise in the percent of LDH-5. A similar disturbance has been demonstrated in 14 polyps, which confirms the known precancerous condition of these lesions. In the uninvolved mucosa surrounding neoplasm, the authors found that the increase in the relative proportion of "type M" isoenzymes, start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…A study of LDH isoenzymes of colon tissues by native gel electrophoresis combined with gel densitometry showed a significant increase in the percentage of LDH-5, which is generally absent in the normal epithelium. By contrast, LDH-1 in cancers was found to be in a steady state or decreased in comparison with normal colonic mucosa [58,59]. Similar results have been achieved in the study of nonsmall cell lung cancer (NSCLC) via immunohistochemistry (IHC).…”
Section: Clinical Significance Of Ldh Isoenzymessupporting
confidence: 70%
See 1 more Smart Citation
“…A study of LDH isoenzymes of colon tissues by native gel electrophoresis combined with gel densitometry showed a significant increase in the percentage of LDH-5, which is generally absent in the normal epithelium. By contrast, LDH-1 in cancers was found to be in a steady state or decreased in comparison with normal colonic mucosa [58,59]. Similar results have been achieved in the study of nonsmall cell lung cancer (NSCLC) via immunohistochemistry (IHC).…”
Section: Clinical Significance Of Ldh Isoenzymessupporting
confidence: 70%
“…The authors deemed the altered LDHA to LDHB ratio as a possible biochemical indicator of an early process of malignant conversion [67]. These conclusions were supported by the data of other investigators who showed high LDHA to LDHB ratios in uninvolved tissues from resection edges that were related to local recurrence possibly due to deep infiltration [58,59,[68][69][70][71]. It is known that LDH-5 overproduction is related exclusively to cancer cells but not to stromal fibroblasts, which have low LDHA expression [72].…”
Section: Clinical Significance Of Ldh Isoenzymesmentioning
confidence: 57%
“…Our data showed a significant increase of total and specific LDH activities in cancer tissues, about 140% of the control. These results were consistent with the reports by CardaAbella et al [6] and Hong et al [7] . Because of the tissue distribution specificity, LDH isoenzymes may be expressed in different levels.…”
Section: Discussionsupporting
confidence: 94%
“…In the ascites supernatant also after cisplatin treatment for 1-2 days, the LDH-5 intensity appeared very dense towards cathode region of the gel which suggests the presence of increased release of LDH-5 from the tumor cells and/or the appearance of the additional isozyme bands. It has been postulated that anaplasia is accompanied by molecular adjustments, which precede morphologic changes in malignancy and may manifest themselves through changes in enzyme patterns, thus, there is predominance of LDH-1 in normal colonic mucosa and of LDH-5 in colonic cancer tissue (Carda-Abella et al 1982).…”
Section: Discussionmentioning
confidence: 99%